Development and preclinical characterization of AMG 329: a human antibody neutralizing FLT3 ligand - Annie Lau-Kilby; Michele Gunsior; Agata Bartczak; Susan Chyou; James Hester; Dorothy Sims; Xiaodong Xiao; Peter Pavlik; Yan Chen; Kerry A. Casey; Kamelia Zerrouki; Qian Wang; et al. (mAbs)
The feline McDonough sarcoma-like tyrosine kinase 3 (FLT3)/FLT3 ligand (FLT3L) signaling pathway regulates the development and activity of dendritic cells (DCs) and other myeloid cells, including monocytes. FLT3L, DCs, and monocytes have been implicated in several autoimmune diseases. Here, we describe the development and characterization of a human immunoglobulin G1λ monoclonal antibody (AMG 329; formerly MEDI1116/VIB-1116/HZN-1116) targeting human FLT3L. AMG 329 was derived from a large human combined antibody display library; it was optimized to enhance affinity for FLT3L and reduce antibody dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity. Binding affinity was determined by surface plasmon resonance interaction analysis. Specificity of FLT3L was measured using cell-based flow cytometry and an in vitro functional neutralization assay. ADCC activity was measured using an in vitro cell culture system. Toxicity and toxicokinetics were evaluated in cynomolgus monkeys during AMG 329 dosing (5–100 mg/kg; ≤ 27 weeks) and recovery (≤32 weeks). The AMG 329 antigen-binding region selectively bound to human and cynomolgus monkey FLT3L with affinities of 170 and 63 pM, respectively. AMG 329 specifically bound to and neutralized soluble and cell-bound human FLT3L and did not induce ADCC. AMG 329 administration generally reduced circulating plasmacytoid, conventional DC, and classical monocyte relative proportions in cynomolgus monkeys in a non–dose-dependent manner. Disruption of the FLT3/FLT3L signaling pathway presents a new potential therapeutic approach to treat autoimmune and inflammatory diseases. AMG 329 is a selective human monoclonal antibody antagonist of FLT3L that is currently being investigated in clinical studies.